2020
DOI: 10.1002/agj2.20453
|View full text |Cite
|
Sign up to set email alerts
|

Irrigated grain sorghum response to 55 years of nitrogen, phosphorus, and potassium fertilization

Abstract: Core Ideas  A 55-yr field study quantified irrigated sorghum response to annual NPK fertilization.  A combination of N and P fertilizers produced the greatest grain yield.  The average economic optimum N rate was ∼ 135 kg N ha −1.  Fertilizer P increased grain yield ~ 2 Mg ha-1 at the economic optimum N rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
(50 reference statements)
1
4
0
Order By: Relevance
“…These results indicated that PN with 120 kg N ha −1 had the greatest effect on sorghum grain yield. This was consistent with the findings of Schlegel and Havlin (2021), who reported that the N rate for the maximum grain sorghum yield would have been 110 kg N ha −1 based on 55 years of continuous field observation [31].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results indicated that PN with 120 kg N ha −1 had the greatest effect on sorghum grain yield. This was consistent with the findings of Schlegel and Havlin (2021), who reported that the N rate for the maximum grain sorghum yield would have been 110 kg N ha −1 based on 55 years of continuous field observation [31].…”
Section: Discussionsupporting
confidence: 92%
“…A high N input could significantly increase the soil inorganic N content, especially in the topsoil layer [35]. As mentioned earlier, the N rate for the maximum grain sorghum yield would have been no more than 110 kg N ha −1 for maximum grain sorghum yield [31], and the extensive use of N fertilizer at 240 kg ha −1 markedly increased soil inorganic N (including nitrate and ammonia nitrogen) accumulation within the 0−60 cm soil layer in the present study. According to Adam et al (2015), sorghum was capable of extracting relatively high quantities of soil N under N-limiting conditions [36]; in this case, an N application rate under 120 kg ha −1 , especially for PN, would satisfy the grain sorghum N demand at the current yield level and reduce soil nutrient losses.…”
Section: Discussionmentioning
confidence: 92%
“…Metho et al reported that the wheat yield upon co-application of N, P, and K was higher than the sum of the yields from individually adding N, P, and K [17]. However, in other studies, the grain yield did not clearly increase after the application of P or K [18,19,39]. Dodd and Mallarino (2005) found that fertilization did not improve corn yield in high P soil until Non−Fertilizer production for 8-9 years [40].…”
Section: Effects Of N P and K Interactions On Root Growthmentioning
confidence: 98%
“…A study on rice-wheat rotation showed that integrating N, P, and K increased the yield and N uptake and decreased N loss in both rice and wheat compared with that obtained upon N or NP application; however, post-application NUE was not significantly different between NPK or NP [18]. Schlegel and Havlin [19] demonstrated that the significantly improved grain yield, N uptake, agronomic N use efficiency (NAE), and N recovery by sorghum in Ulysses silt loam upon the coapplication of N, P, and K was mainly due to N and P, rather than adding K. The continuous application of N, P, and K over 13 years in sandy loam increased the yield and apparent N recovery of spring barley; however, the increase was not significant [20]. Studies have suggested that the combination of fertilizers does not affect N utilization [21,22].…”
Section: Introductionmentioning
confidence: 97%
“…Plant nutrition directly affects the effective synthesis, distribution, and accumulation of components of plants, thereby resulting in variations in quality under different cultivation conditions [17,18]. Rational fertilization increases the yield and quality as well as increasing the N and K use efficiency [19][20][21][22]. However, applying excessively high or low amounts of fertilizer will inhibit the absorption of nutrients, which is not conducive to growth.…”
Section: Introductionmentioning
confidence: 99%